Emerging technologies [drug eluting stents]. - Panescu, D.
Two main contributing factors to plaque formation and growth. One relates to the triggering role played by inflammatory mediators, such as cytokines. The second relates to the out-of-control growth of smooth-muscle cells. The drug selected to work with a drug-eluting stent should control one or both of these factors. Typically, the drug is entrapped in a polymer coating that slowly releases it into the arterial wall. Polymer materials include bioerodible polymers, such as poly-L lactic acid, and biostable polymers, such as polyurethane derivates and silicone-based polymers.
Keywords: Bioerodible polymers; Cytokines; Drug; Drug-eluting stent; Inflammatory mediators; Plaque formation; Plaque growth; Polymer coating entrapped drug; Polymer materials; Smooth-muscle cells